Legacy of Sanitary Nurses in the Care of Chilean Health [el Legado de Las Enfermeras Sanitarias en el Cuidado de la Salud Chilena] - Nunez-Carrasco, E (Universidad de Concepcion, 2017)
During the early twentieth century, Chile shows a social crisis that impacted on the health conditions of the vast majority of the population, and it is during this period that the first steps towards the professionalization of nursing are taken and the sanitary nurse training begins. Objective: Describe the care practices provided by health nurses in Chile that marked the transformation of the health conditions of the population. Method: From the life stories of the nurses who worked in the health services in Chile, before and during the decade of the 1970s, the identity of the health-care nurses trained in the 1920s was first characterized, and then the legacy of the socio-cultural care applied in the communities was interpreted. Results: The care was supported by a socio-cultural network and it is the health nurses who operationalized the health macro-policies. Conclusion: The construction of the identity of health nurses emerges as a transversal axis throughout this period, and they are recognized for the urgency with which they assumed the intervention of health needs and for their ethical commitment to safeguard the care of individuals, families and communities. © 2017, Universidad de Concepcion. All rights reserved.